Structure of Woody Plant Communities on Mudflats of Species to the Coast and Dykes Protection: As Case Study in Sea West of Kien Giang Province - Mo Danh; Luom Thanh Thai; Bao Manh Ngoc Nguyen (Research in Ecology, 2025)
This study is proposed by Kien Giang University to the Ministry of Education and Training with the aim investigate species abundant in the Mekong Delta to develop land in Vietnam. Western Mekong Delta (WMD) alluvium sediments flows from upstream China to Vietnam. This sediments accumulated gradually elevation the new land. The coastal where mangrove forests with a rich ecosystem of plants and animals. Over time, these forests change, with different plant species succeeding each other. Biodiversity of tree species, and abundance communities, measured growth of the forest in this region. In 2023, a comprehensive survey was conducted. Investigate the situation of woody plant species in mangrove forests in sub-regions. The methods investigate is indentified the number of survey plots have done depend on the density of the forest, Base on the width of the forest range, the number of survey plots in sub region set up from 10 to 15 plots. In total, 68 plots have done established, plot is 100 square meters. Found the number of species in each ecological region and growth situation. The results of study are provided scientifically based information of the tree species composition, distribution, and community structures; this result had 16 species from 11 plant families is determined. Among these species have 6 dominant species. Main discovery is found two species grow on the best on new land were Avicennia officinalis and Avicennia alba can develope on the original new land. These adapted species can exploit food and medicinal herbs in biodiversity distribution abundance of these species. It can help Vietnam by mearsures using the species Aviecennia be discovered will promote sea reclamation faster instead of letting the natural law of sea reclamation follow. Conclusion there are 7 species in high land, 11 species medium land, 8 species low land 6 species lowest land, of which 2 species found that can planting in this area in target for land reclamation in this area.